Star anise (Illicium verum Hook. f.) essential oil: Antioxidant properties and antibacterial activity against Acinetobacter baumannii. (24th April 2019) - Luís, Ângelo; Sousa, Sónia; Wackerlig, Judith; Dobusch, Daniel; Duarte, Ana Paula; Pereira, Luísa; Domingues, Fernanda
Abstract: The increased resistance of pathogenic bacteria to multiple antimicrobial agents is becoming a significant public health threat. For many pathogenic bacteria there are already limited or no effective antimicrobials available to treat the infections caused by them. Acinetobacter baumannii is a Gram‐negative, biofilm‐forming, nonmotile coccobacillus and a major human pathogen causing hospital‐acquired infections, such as ventilator‐associated pneumonia, bacteraemia, meningitis, and urinary tract and wound infections. There is therefore a clear need to discover new compounds and strategies to overcome widespread antimicrobial resistance, with a focus on A. baumannii strains. Star anise ( Illicium verum Hook. f.) has been widely used as an ingredient in traditional Chinese cooking, as a flavouring agent, and as a medicine for over 3000 years; however, the essential oil (EO) isolated from star anise has not been further characterized in terms of its bioactivities and potential applications. In this work, a screening of the biological properties of star anise EO together with its chemical characterization were performed. Special attention was given to the impact of this EO in the formation of biofilms by A. baumannii . It was demonstrated that star anise EO is able to scavenge free radicals, to inhibit lipid peroxidation, and to inhibit protein denaturation, which is associated with its antioxidant and anti‐inflammatory properties. Moreover, the effects of the EO on the planktonic and biofilm cells of A. baumannii, inhibiting the formation of biofilms, dispersing preformed biofilms, and decreasing the capacity of the bacterial cells to adhere to polystyrene, together with its ability to inhibit quorum sensing, were also demonstrated. Abstract : A screening of the biological properties of star anise essential oil, together with its chemical characterization were performed. Special attention was given to the impact of this essential oil in the formation of biofilms by Acinetobacter baumannii .